La historia social evolutiva de la criminalidad y de los sistemas de justicia penal - Emsley, Clive (Revista de historia., 2003)
In this article, the author explains how research on criminal history were carried out since the 1960s, making special emphasis on the new approaches on violence and the various instruments used by the State to execute power, such as the judicial system. Furthermore, Emsley makes an exceptional analysis of the works published in Western Europe, particularly in Great Britain.